Preparing for the IBDP: A Qualitative Evaluation of the Cambridge IGCSE Experience in ACS Jakarta - Sugiarto, Lily Yuliani; Sugiarto, Sugiarto; Santosa, Heru (International Education Trend Issues, 2025)
This study examines the implementation of the Cambridge International General Certificate of Secondary Education (IGCSE) curriculum at ACS Jakarta and its effectiveness in preparing students for the International Baccalaureate Diploma Programme (IBDP). With growing demand for international curricula in Indonesia’s Satuan Pendidikan Kerja Sama (SPK) schools, the study evaluates how IGCSE supports academic transition to IBDP. Using the CIPP (Context, Input, Process, Product) evaluation model, qualitative data were collected through interviews with school leaders, teachers, students, alumni, and parents. Findings show that while IGCSE provides strong academic grounding and subject continuity, it does not fully equip students with the research, writing, and independent learning skills required in IBDP. Stakeholders identified the need for better instructional alignment, skill-based scaffolding, and student-centered academic guidance. The study contributes to understanding international curriculum pathways in SPK schools and offers recommendations to strengthen the IGCSE-to-IBDP transition.